An optical PUF based on Raman signal, preparation method and use thereof

By embedding nanosilicon dioxide at similar Raman signal peak positions in the PDMS matrix to form a composite film, the problem that PDMS cannot participate in the generation of anti-counterfeiting signals in optical PUF is solved, and the efficient anti-counterfeiting performance and accuracy of the biochip are achieved, which is suitable for large-scale Large-scale production.

CN118909444BActive Publication Date: 2025-01-03ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411398541.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-03
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

When the existing optical PUF is prepared by PDMS, the optical anti-counterfeiting signal comes from the incorporation of materials, which causes interference to the work of the biochip, reducing the accuracy and reliability of the biochip. Moreover, PDMS is only used as a matrix material and cannot participate in the generation of anti-counterfeiting signal. , cannot meet the anti-counterfeiting needs of biochips.

Method used

By embedding nanosilicon dioxide similar to its Raman signal peak in the PDMS matrix, a composite film is formed, so that the Raman signals of nanosilicon dioxide and PDMS are superimposed together through interaction to generate a composite Raman signal, and the optical PUF is realized. Anti-counterfeiting performance while ensuring the accuracy and reliability of biochips.

Benefits of technology

An optical PUF with excellent anti-counterfeiting performance is realized, overcoming the limitation that PDMS can only be used as a matrix material in the prior art, reducing production costs, suitable for large-scale production, and compatible with biochip preparation processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118909444B_ABST
    Figure CN118909444B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of optical PUF technology, and discloses an optical PUF based on Raman signals, a preparation method and use thereof, wherein the optical PUF comprises a nano-material composite film layer, wherein the nano-material composite film layer is a composite film formed by randomly embedding nano-silicon dioxide in polydimethylsiloxane, wherein the nano-silicon dioxide is an amorphous material; the mass ratio of the polydimethylsiloxane to the nano-silicon dioxide is 400:1 to 10000:1; the optical anti-counterfeiting signal of the optical PUF is generated from the composite Raman signal of the nano-silicon dioxide and the polydimethylsiloxane, and there is a difference in the Raman signal intensity at the peak of the Raman signal of polydimethylsiloxane at any different position on the nano-material composite film layer. The present invention utilizes the composite Raman signal of the SiO2 / PDMS composite film to realize an optical PUF with excellent anti-counterfeiting performance without affecting the accuracy and reliability of the biochip.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optical PUF, and in particular to an optical PUF based on Raman signals, and a preparation method and application thereof. Background Art

[0002] Microfluidic biochips have revolutionized biomedical applications such as amplification platforms, biomolecular recognition, antigen detection, and personalized cancer therapy due to their advantages such as small sample volumes, fast biochemical reactions, and high system throughput, and have driven the development of global healthcare. The surge in demand for diagnostic tests has further developed new microfluidic biochip technologies and solutions, with millions of biochips used for COVID-19 testing being used every day in hospitals, primary healthcare facilities, workplaces, and people's homes around the world. In addition, the global microfluidics market is expected to be worth $58.8 billion, with a compound annual growth rate (CAGR) of 23.2%. The biochip market is expected to have a CAGR of 13.9% during the 2022–2027 forecast period. To ensure economies of scale and reduce costs, biochip companies have used outsourcing and horizontal supply chain models for goods and services, which involve untrusted third-party partners, resulting in biochips that may be subject to malicious attacks by criminals. As a result, attacks on microfluidic biochips have become a growing threat. The severity of such attacks lies in the potential for harm to patients, damage to healthcare, waste of resources, and negative economic consequences. In order to maintain the reliability, confidentiality and trustworthiness of biochips, anti-counterfeiting measures need to be taken for biochips. Among the commonly used anti-counterfeiting methods, there are various protective labels: radio frequency identification (RFID) tags, barcodes, holograms, watermarks, protective inks, etc. Due to the deterministic encoding and corresponding decoding mechanisms of these methods, these anti-counterfeiting labels have the risk of being cracked by machine learning.

[0003] Physical Unclonable Function (PUF) is an ideal anti-counterfeiting label because of its anti-cloning, cost-effectiveness, and resistance to various physical attacks. Physical Unclonable Function (PUF) is a secure hardware that converts input stimulus (challenge) into output response (response) through a physical system. This conversion method is specific to the exact hardware instance (unique) and cannot be copied (non-clonable). Over the years, people have developed a variety of PUFs including optical PUF, magnetic PUF, and electrical PUF. Among them, optical PUF has attracted widespread attention due to its advantages of huge amount of encoded data and high output complexity. In addition, optical PUF has been proven to be the most powerful PUF due to its complex input / output unpredictability and identifiable information content. Therefore, applying optical PUF to anti-counterfeiting labels of biochips is a safe and efficient anti-counterfeiting method. Optical PUF requires that the optical signals at different positions have obvious differences (i.e., the spectra of the optical signals generated at different positions do not overlap, and the difference between the optical signals at any different positions indicates that the greater the randomness of the signal generation, the better the anti-counterfeiting performance. In the present invention, the anti-counterfeiting signal (i.e., the anti-counterfeiting feature) refers to various signals that can achieve a unique excitation-response pair, and the optical anti-counterfeiting signal refers to an optical signal that can achieve a unique excitation-response pair, including but not limited to: fluorescence, phosphorescence, laser, Raman signal (Raman signal), etc.; Physical unclonability means that each PUF has unique characteristics due to differences in its physical properties, and these characteristics cannot be completely copied or cloned during the manufacturing process. The optical PUF described in the present invention refers to an anti-counterfeiting label that directly generates a unique optical anti-counterfeiting signal under specific excitation conditions by utilizing the inherent physicochemical properties of a material or a combination of materials. The optical signal of the optical PUF originates from the inherent physicochemical properties of the material itself and does not rely on the reflection, refraction or transmission of an external light source. An optical PUF based on Raman signals refers to an optical PUF that is identified and verified by the unique Raman signal generated by a material or a combination of materials when irradiated with excitation light (usually a laser). These Raman signals reflect the vibration modes of the molecules inside the material and are directly derived from the molecular structure and chemical composition of the material, without relying on the reflection, refraction or transmission of an external light source.

[0004] Published data show that 55% of the fabricated devices are made of polydimethylsiloxane (PDMS), a transparentthermosetting polymer. Ongaro AE, Ndlovu Z, Sollier E, et al. Engineering a Sustainable Future for Point-of-Care Diagnostics and Single-Use Microfluidic Devices[J]. Lab on a Chip, 2022, 22(17): 3122–3137.). Compared with other polymers, PDMS has the following attractive properties: optical transparency, biocompatibility, gas permeability, and non-toxicity. Therefore, the microfluidics community has accepted the use of PDMS to construct microfluidic biochips. In order to be compatible with the materials of biochips, optical PUFs used for biochip anti-counterfeiting also need to be prepared with PDMS. At present, many researchers have prepared optical PUFs by doping PDMS with materials that can generate optical signals. In these studies, some optical PUFs use fluorescence, phosphorescence, and laser signals as optical anti-counterfeiting signals, and some use Raman signals as optical anti-counterfeiting signals. It should be made clear that the anti-counterfeiting properties of structural color films and photonic crystals prepared using PDMS in the prior art rely on the reflection and refraction of external light sources, rather than the optical signals generated by the material itself, and do not belong to the optical PUF defined in the present invention. The optical signal generated by the material itself refers to the optical response independently emitted by the material under the excitation conditions, which can be optical excitation, thermal excitation, electrical excitation, etc. The optical response includes but is not limited to fluorescence signals, phosphorescence signals, laser signals, Raman signals, etc. The optical response is directly generated by the energy transition of the internal electrons or molecular structures of the material under the excitation, and can be detected by fluorescence spectrometers, Raman spectrometers, etc., which is completely different from the signal generated by the reflection (reflection) or refraction (refraction) of the external light source.

[0005] In optical PUFs that use fluorescence, phosphorescence, and laser signals as optical anti-counterfeiting signals, since PDMS itself does not generate fluorescence, phosphorescence, or laser signals, PDMS only serves as a matrix and does not contribute to the anti-counterfeiting features. The fluorescence, phosphorescence, and laser signals all come from the doped materials (There was no PL signal in the pristine PDMS sample. Ogawa H, Shibuya T, Moriai Y, et al. Correlation between chemical structural changes and laser fluence in femtosecond laser processing of polydimethylsiloxane[J]. Applied Physics A: Materials Science and Processing, 2022, 128(9): 1–7.). For example, Chen et al. prepared a new SiNCs / PDMS anti-counterfeiting coating by dispersing silicon nanocrystals (SiNCs) in PDMS. This optical PUF uses the fluorescence signal of SiNCs as an anti-counterfeiting feature. Kumar et al. dispersed phosphor powder in a PDMS matrix to prepare an optical PUF, which used the phosphorescence signal of the phosphor powder as an anti-counterfeiting feature.

[0006] In optical PUFs that use Raman signals as optical anti-counterfeiting signals, existing literature uses the Raman signals of incorporated materials for anti-counterfeiting. PDMS is only used as a matrix material. Therefore, the Raman signal peaks of the incorporated (incorporated / incorporating) materials are selected to be far away from the Raman signal peaks of PDMS to deliberately avoid the Raman signal of PDMS (the Raman signal peak of PDMS is usually 490±5 cm -1 ), to ensure that the anti-counterfeiting signal comes only from the doped material rather than PDMS. For example, Guo et al. doped diamonds containing nitrogen vacancy color centers into PDMS to realize an optical PUF with multiple anti-counterfeiting functions. The optical PUF uses various signals of diamonds containing nitrogen vacancy color centers as anti-counterfeiting features. The figure in the paper shows that the Raman signal of the doped material and the Raman signal of PDMS are far apart and do not overlap (see Fig. 27 ), the Raman signal peak of diamond in this figure is 1330 cm -1 The Raman signal peak of PDMS is usually 490±5 cm -1, the two are far apart and will not overlap, so PDMS does not participate in the generation of anti-counterfeiting signals (PUF labels are prepared by embedding microdiamonds into polydimethylsiloxane (PDMS) flexible substrateswith three different concentrations of the NV color center. Guo H, Qin Y,Wang Z, et al. Multilevel Encoding Physically Unclonable Functions Based onThe Multispecies Structure in Diamonds[J]. Advanced Functional Materials,2024, 34(15): 2304648.). Further explanation: In the optical PUF using Raman signals as anti-counterfeiting signals, the basis for judging that PDMS is only used as a matrix and does not participate in the generation of anti-counterfeiting signals is that there is no difference in the intensity of the Raman signal generated by pure PDMS (without other materials) (see Fig.18 ), the indifference of Raman signal intensity means that the Raman signals generated by pure PDMS at any different positions basically overlap; when the Raman signal peak of the material doped in the PDMS matrix is ​​far away from the Raman signal peak of PDMS, it will not overlap with the Raman signal of pure PDMS, which means that PDMS does not participate in the generation of anti-counterfeiting signals. Therefore, the prior art provides a technical inspiration that when using PDMS to prepare optical PUF, the Raman signal peak of the selected doped material must be far away from the PDMS Raman signal peak.

[0007] In summary, the optical anti-counterfeiting signals of the existing optical PUFs prepared with PDMS all come from the incorporated materials, and the selection criteria for the incorporated materials are that the Raman signal peak of the incorporated materials must be far away from the PDMS Raman signal peak to avoid interference with the PDMS Raman signal. PDMS is only a matrix material and does not participate in the generation of anti-counterfeiting signals. However, since the optical anti-counterfeiting signals come from the materials incorporated in PDMS, the optical anti-counterfeiting signals generated by these incorporated materials will interfere with the work of the biochip, reduce the accuracy and reliability of the biochip, and make the existing optical PUF unable to be applied to the biochip. Therefore, it is of great value to study an optical PUF with good anti-counterfeiting performance that does not affect the accuracy and reliability of the biochip. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention provides an optical PUF based on Raman signals. After a long period of hard work and exploration, the inventor unexpectedly selected a Raman signal peak position (usually 490±5 cm -1 ) similar nano-silicon dioxide (Raman signal peak is usually 490±5 cm -1 ), nano-silicon dioxide (SiO2) is randomly embedded in polydimethylsiloxane (PDMS) to form a composite film. The Raman signals generated by nano-silicon dioxide (SiO2) and the PDMS matrix are synergistically superimposed through interaction to form a composite Raman signal, so that the composite Raman signal intensity at any different position on the optical PUF at the peak of the Raman signal of polydimethylsiloxane is different, and the composite Raman signal of SiO2 and PDMS in the SiO2 / PDMS composite film is unexpectedly realized, and an optical PUF with excellent anti-counterfeiting performance and no influence on the accuracy and reliability of the biochip is realized. The present invention overcomes two technical biases of the prior art: first, it overcomes the technical bias that the prior art believes that when using PDMS to prepare an optical PUF, a material far away from the PDMS Raman signal peak must be selected as an incorporated material to realize optical signal anti-counterfeiting; second, it overcomes the technical bias that PDMS can only be used as a matrix material in the existing optical PUF. It is currently the only optical PUF that uses the PDMS Raman signal for anti-counterfeiting. So far, no research has been found on using the Raman signal generated by PDMS as an anti-counterfeiting feature of the optical PUF. The optical PUF preparation process of the present invention is compatible with the existing biochip preparation process, has low cost, is suitable for large-scale production, and has great application prospects.

[0009] The present invention adopts the following technical solution:

[0010] The present invention provides an optical PUF based on Raman signals, wherein the optical PUF comprises a nano-material composite film layer, wherein the nano-material composite film layer is a composite film formed by randomly embedding nano-silicon dioxide in polydimethylsiloxane, wherein the transmittance of the nano-material composite film layer and the polydimethylsiloxane in the wavelength range of 300 to 800 nm is ≥90%; the nano-silicon dioxide is an amorphous material; the mass ratio of the polydimethylsiloxane to the nano-silicon dioxide m(PDMS):m(SiO2) is 400:1 to 10000:1;

[0011] The optical anti-counterfeiting signal of the optical PUF is generated from the composite Raman signal of the nano-silica and the polydimethylsiloxane. There are differences in the Raman signal intensity at the peak of the polydimethylsiloxane Raman signal at any different position on the nano-material composite film layer. The composite Raman signal refers to the Raman signal generated by the nano-silica (SiO2) randomly embedded in the polydimethylsiloxane (PDMS) matrix and the PDMS matrix itself under the excitation condition. The Raman signal generated by the PDMS matrix is ​​synergistically superimposed through interaction, resulting in the composite Raman signal having obvious intensity differences at any different position. Fig. 20 As shown, this obvious difference in Raman signal intensity is highly complex and unpredictable, and thus can be used for anti-counterfeiting. The composite Raman signal can be detected by a Raman signal detection instrument with a surface scanning function, such as a Raman spectrometer.

[0012] The Raman signal (also called Raman shift) of the present invention can be detected by a Raman signal detection instrument with a surface scanning function.

[0013] The Raman signal refers to the Raman spectrum measured under the condition of excitation (challenge), and is a value obtained by performing a single integration process on the Raman spectrum.

[0014] The challenge condition of the SiO2 / PDMS composite film is a laser with a central emission wavelength of 300 to 600 nm; preferably, the challenge condition is a laser with a central emission wavelength of 532 nm;

[0015] In the present invention, the nano silicon dioxide (SiO2) of the present invention is randomly embedded or incorporated into polydimethylsiloxane (PDMS), and the two form a composite film. The random embedding (Embedding) or incorporation (incorporating / incorporating) means that the nano silicon dioxide (SiO2) is randomly and unevenly dispersed in the PDMS matrix to form a composite film, and there is no obvious stratification between the nano silicon dioxide (SiO2) and PDMS under a scanning electron microscope.

[0016] SiO2 alone is difficult to attach directly to the surface of a biochip for anti-counterfeiting applications, so an independent layer formed by a single material cannot be used for biochip anti-counterfeiting. The optical signals of a single PDMS Raman signal at different locations have no obvious difference (i.e., the spectra of the Raman signals generated at different locations are almost the same), such as Fig.19As shown, PDMS alone cannot be used for biochip anti-counterfeiting. However, the present application forms a composite film of SiO2 and PDMS, and the embedding of SiO2 makes the optical signals of PDMS Raman signals at any different positions have obvious differences (that is, the spectra of Raman signals generated at different positions do not overlap), as shown in FIG. Fig. 20 As shown, it can be used for anti-counterfeiting of biochips.

[0017] For example, in the prior art, such as structural color films and photonic crystals for anti-counterfeiting, a common design is to use SiO2 and PDMS as two independent layers, that is, the SiO2 layer and the PDMS layer are separated independently, rather than embedding SiO2 in PDMS to form a composite film layer. The anti-counterfeiting principle of structural color films is that their anti-counterfeiting signals originate from the reflection and refraction of external light signals, rather than signals generated by the material itself. In addition, this independent layered structure makes it impossible for materials to form microscopic interactions, resulting in the inability to generate complex Raman signals or anti-counterfeiting identification functions. Even if the Raman signal is detected, there is no difference in the intensity of the generated Raman signal, so it cannot be used as the optical PUF based on Raman signals described in the present invention (see Comparative Example 4).

[0018] The present invention forms the nano-material composite thin film layer by embedding a specific proportion of nano-silicon dioxide in the PDMS matrix. The nano-silicon dioxide can interact with the Raman signal of PDMS to form a composite Raman signal, so that any different position on the optical PUF is at the peak position of the Raman signal of polydimethylsiloxane (usually 490±5 cm -1) have different Raman signal intensities. Nano-silica is randomly embedded and dispersed in the PDMS matrix. The randomness and non-uniformity of this dispersion can effectively scatter the incident laser, increasing the complexity of the optical path, making the composite Raman signal of the composite film highly complex and unpredictable in spatial distribution, making the information extracted from these signals highly unique and difficult to replicate, and realizing an optical PUF with excellent anti-counterfeiting performance without affecting the accuracy and reliability of the biochip. The composite Raman signal generated by the nano-silica randomly embedded in the PDMS matrix and the PDMS matrix of the present invention can produce a unique optical PUF anti-counterfeiting performance, which mainly comes from the interaction of three aspects: (1) Optical scattering enhancement: When subjected to excitation conditions such as laser conditions, the nano-silica particles can introduce additional optical scattering centers in the PDMS matrix. This scattering can change the path length of the optical path, thereby changing the intensity of the composite Raman signal. (2) Microstructure heterogeneity: Due to the random distribution of nano-silica particles, the microenvironment of the PDMS matrix has changed, resulting in changes in the local environment of the Raman active groups (such as Si-O-Si chains), thereby affecting their vibration modes and, in turn, affecting the Raman signals of PDMS. (3) The specific proportion and crystalline nano-silica of the present invention can be synergistically superimposed with the Raman signals of PDMS. The superposition of the Raman signals of the two significantly enhances the complexity and unpredictability of the Raman signals generated at any different point on the optical PUF, thereby achieving better anti-counterfeiting performance. Therefore, the optical PUF technology of the present invention uses PDMS not only as a base material, but also participates in the generation of anti-counterfeiting signals, overcoming the technical bias that PDMS in existing optical PUFs can only be used as a base material and cannot participate in the generation of anti-counterfeiting signals.

[0019] Therefore, the present invention utilizes the Raman signals generated by SiO2 and PDMS in the SiO2 / PDMS composite film, enhances the complexity of the Raman signal of the PDMS film by means of non-uniformly distributed nano-SiO2 particles, and utilizes the SiO2 / PDMS composite film to realize a security label that is difficult to copy. The optical PUF technology of the present invention not only utilizes PDMS as a base material, but also participates in the generation of anti-counterfeiting signals, thus overcoming the technical prejudice that PDMS in the existing optical PUF can only be used as a base material but cannot participate in the generation of anti-counterfeiting signals. In addition, the nano-material composite film layer and the polydimethylsiloxane have extremely high transmittance, are suitable for anti-counterfeiting of biochips, and will not affect the accuracy and reliability of the biochips.

[0020] In one embodiment of the present invention, the nano-silicon dioxide is spherical in shape with an average diameter of 20 to 300 nm; in the present invention, the "spherical" nano-silicon dioxide we mentioned refers to its appearance being roughly spherical under a scanning electron microscope, but does not exclude the existence of tiny geometric irregularities, such as slightly flat, angular or incompletely rounded surfaces. Specifically, we define the nano-silicon dioxide (SiO2) in the nano-material composite film layer as spherical, which means that more than 90% of the nano-silicon dioxide particles are in a shape under a scanning electron microscope, and the ratio of the maximum and minimum diameters of these nano-silicon dioxide particles should not be greater than 1.2.

[0021] In one embodiment of the present invention, the substrate is selected from materials with a transmittance of ≥90% in the wavelength range of 300-800 nm; for example, it may be quartz glass, sapphire (Al2O3), borosilicate glass, magnesium fluoride, and calcium fluoride.

[0022] In one embodiment of the present invention, the average value of the bit uniformity of the optical PUF is between 0.49 and 0.51;

[0023] The calculation formula of the bit uniformity (BU) is:

[0024]

[0025] in, s The number of bits per key, i.e. the number of bits per optical PUF output, K l express s The bit array l bit response;

[0026] In one embodiment of the present invention, the average value of the similarity of the different optical PUFs is between 49% and 53%, and the average value of the inter-chip Hamming distance is between 0.4 and 0.6;

[0027] In one embodiment of the present invention, the average value of the similarity of the same optical PUF is between 90% and 100%, and the average value of the intra-chip Hamming distance is between 0 and 0.2;

[0028] The calculation formula of the similarity index (SI) is:

[0029]

[0030] in, C is the matrix difference of the two optical PUF images after binarization. The digitized matrix of the two PUF images can be expressed as: , , A and B represent the digitized matrices of two optical PUF images, which represent the binary data of the images, where the value of each pixel is 0 or 1; C 0 is a matrix C The number of "0" in a mn and b mn is the pixel value at the corresponding position, where m represents the row number and n represents the column number.

[0031] The calculation formula of the inter-chip Hamming distance (Inter Hamming Distance, Inter-HD) is:

[0032]

[0033] in, q represents the total number of different optical PUFs, s represents the number of bits per key, i.e. the number of bits per optical PUF output, HD(K i , K j ) :Indicates the i and j An optical PUF is generated s Bit Key K i and K j The Hamming distance between

[0034] The calculation formula of the intra-chip Hamming distance (Intra-HD) is:

[0035]

[0036] in, m Indicates the number of repeated measurements, that is, the total number of times the optical PUF is tested. s represents the number of bits of each key, HD(K i , K i,t ) Represents the original key K i with t The key obtained from the measurement K i,t The Hamming distance between .

[0037] The present invention provides a method for preparing an optical PUF based on a Raman signal as described above, and the preparation method comprises the following steps:

[0038] Step (1) mixing an alcohol solution, ammonia water (NH3·H2O) and deionized water to form a mixed solution, wherein the concentration of the ammonia water is 0.5 to 1 M, then adding methyl orthosilicate (TMOS) to the mixed solution in a volume ratio of 1:100 to 1:10, continuously stirring to obtain a milky white suspension, centrifuging to separate a solid, and then drying to obtain SiO2 nanoparticles;

[0039] In one embodiment of the present invention, the alcohol solution is methanol or ethanol; in another embodiment of the present invention, the alcohol solution is methanol;

[0040] In one embodiment of the present invention, the amount of the alcohol solution added is 0.5 to 3 moles;

[0041] In one embodiment of the present invention, the concentration of the ammonia water is 0.5 M;

[0042] In one embodiment of the present invention, the stirring speed for forming the mixed solution is 200 to 1200 rpm;

[0043] In one embodiment of the present invention, the volume ratio of methyl orthosilicate (TMOS) to the mixed solution is 1:60;

[0044] In one embodiment of the present invention, the amount of methyl orthosilicate (TMOS) added is 0.5 to 3 mL;

[0045] In one embodiment of the present invention, stirring is continued for 0.5 to 3 hours to obtain the milky white suspension;

[0046] In one embodiment of the present invention, the milky white suspension is centrifuged at 5000 to 10000 rpm for 5 to 20 minutes;

[0047] In one embodiment of the present invention, the drying temperature is 50-150°C; in another embodiment of the present invention, the drying temperature is 80°C;

[0048] In one embodiment of the present invention, the drying time is 0.5 to 3 hours;

[0049] Step (2) polydimethylsiloxane (PDMS) and a curing agent are mixed in a volume ratio of 5:1 to 20:1, and then the SiO2 nanoparticles are added to the mixture of PDMS and the curing agent in a mass ratio of m(PDMS) to m(SiO2) of 400:1 to 10000:1 to obtain a SiO2 / PDMS mixture, and then the SiO2 / PDMS mixture is spin-coated onto a substrate at a speed of 3000 to 10000 rpm, and then heated at 40 to 100°C to form a SiO2 / PDMS composite film.

[0050] In one embodiment of the present invention, the curing agent is a curing agent material known in the art, such as methyltrichlorosilane, trisilane, phenyltrichlorosilane, and the like.

[0051] In one embodiment of the present invention, the volume ratio of the PDMS to the curing agent is 10:1;

[0052] In one embodiment of the present invention, m(PDMS):m(SiO2)=9650:1;

[0053] In one embodiment of the present invention, the SiO2 nanoparticles are prepared as a SiO2 ethanol solution with a concentration of 0.5 to 10 mg / mL and added to a mixture of PDMS and a curing agent;

[0054] In one embodiment of the present invention, the volume of the SiO2 nanoparticle ethanol solution added to the mixture of PDMS and the curing agent is 0.5 to 5 mL;

[0055] In one embodiment of the present invention, the substrate is selected from materials with a transmittance of ≥90% in the wavelength range of 300-800 nm. In another embodiment of the present invention, the substrate is any one of quartz glass, sapphire (Al2O3), borosilicate glass, magnesium fluoride, and calcium fluoride; more preferably, quartz glass.

[0056] In one embodiment of the present invention, the spin coating speed of the SiO2 / PDMS mixture is 4000 rpm;

[0057] In one embodiment of the present invention, the acceleration of the spin coating speed of the SiO2 / PDMS mixture is 100 to 600 rpm;

[0058] In one embodiment of the present invention, the spin coating time is 45 to 120 seconds;

[0059] In one embodiment of the present invention, the heating temperature of the SiO2 / PDMS composite film is 80°C.

[0060] In one embodiment of the present invention, the heating time of the SiO2 / PDMS composite film is 20 to 60 minutes, more preferably 30 minutes.

[0061] The preparation method of the present invention is compatible with the existing biochip preparation process, has a simple process and low cost, so that the optical PUF of the present invention can be directly integrated into the existing biochip preparation process line, greatly reducing the production cost, having significant innovation and practical value, and the optical PUF of the present invention has great application prospects.

[0062] Furthermore, the present invention also provides an anti-counterfeiting label, which comprises the optical PUF based on Raman signals as described above or the optical PUF based on Raman signals prepared by the preparation method as described above, and is particularly suitable for an anti-counterfeiting label on a biochip.

[0063] Furthermore, the present invention provides an optical PUF based on Raman signals as described above, an optical PUF based on Raman signals obtained by the preparation method as described above, and a use of the anti-counterfeiting label as described above in the field of anti-counterfeiting.

[0064] The Raman signal-based optical PUF of the present invention is prepared by a low-cost spin-coating process. In addition, the spin-coating process is compatible with the preparation process of biochips, so that the optical PUF of the present invention can be directly integrated into the existing biochip preparation process line, which is suitable for large-scale production. In addition, the preparation cost of the optical PUF of the present invention is 10 -6 USD / piece (40 μm × 40 μm) (Table 1), which is lower than the cost of other existing optical PUFs of the same area (Table 2). It has cost advantages and is conducive to large-scale industrial applications.

[0065] The beneficial effects of the present invention are:

[0066] In view of the shortcomings of the prior art, the present invention provides an optical PUF with a Raman signal. Surprisingly, the present invention selects a Raman signal peak position (usually 490±5 cm -1 ) similar nano-silicon dioxide (Raman signal peak is usually 490±5 cm -1), nano-silicon dioxide (SiO2) is randomly embedded in polydimethylsiloxane (PDMS) to form a composite film, and the Raman signals generated by the nano-silicon dioxide (SiO2) and the PDMS matrix are synergistically superimposed through interaction to form a composite Raman signal, so that the Raman signal intensity at the peak of the Raman signal of polydimethylsiloxane at any different position on the optical PUF is different. The composite Raman signal of the SiO2 / PDMS composite film is used to realize an optical PUF with excellent anti-counterfeiting performance and does not affect the accuracy and reliability of the biochip; and the preparation process of the present invention is compatible with the existing biochip preparation process, has low cost, is suitable for large-scale production, has great application prospects, and overcomes the technical prejudice that PDMS can only be used as a matrix material in the existing optical PUF.

[0067] (1) The present invention overcomes two technical biases of the prior art: first, it overcomes the technical bias of the prior art that when using PDMS to prepare optical PUF, materials far away from the PDMS Raman signal peak must be selected as the doping material to achieve optical signal anti-counterfeiting; second, it overcomes the technical bias that PDMS can only be used as a matrix material in the existing optical PUF. The present invention forms the nanomaterial composite film layer by embedding a specific proportion of nano-silicon dioxide in the PDMS matrix. The nano-silicon dioxide can be close to the Raman signal peak of PDMS, and a composite Raman signal is formed through synergistic superposition through interaction, so that any different position on the optical PUF is close to the Raman signal peak of polydimethylsiloxane (usually 490±5 cm -1 ) have different composite Raman signal intensities, and the complexity of the Raman signal of the PDMS film is enhanced by the non-uniform distribution of nano-SiO2 particles ( Fig.21 ), using SiO2 / PDMS composite film to achieve a difficult-to-copy security label ( Fig. 22 ). The average bit uniformity of the optical PUF of the present invention is between 0.49 and 0.51, the average similarity of different optical PUFs is between 49% and 53%, the average Hamming distance between chips is between 0.4 and 0.6, the average similarity of the same optical PUF is between 90% and 100%, and the average Hamming distance within the chip is between 0 and 0.2, achieving excellent anti-counterfeiting performance. The optical PUF technology of the present invention uses PDMS not only as a base material, but also participates in the generation of optical anti-counterfeiting signals. This method has not been reported in existing literature and is highly innovative.

[0068] (2) The optical PUF preparation method of the present invention is compatible with the existing biochip preparation process, and the process is simple and low-cost, so that the optical PUF of the present invention can be directly integrated into the existing biochip preparation process line, greatly reducing the production cost and facilitating large-scale industrial application.

[0069] Therefore, the optical PUF of the present invention utilizes the composite Raman signal of the SiO2 / PDMS composite film based on the Raman signal to achieve an optical PUF with excellent anti-counterfeiting performance without affecting the accuracy and reliability of the biochip. Its preparation process is compatible with the existing biochip preparation process, has low cost, is suitable for large-scale production, has great application prospects, and overcomes the technical prejudice that PDMS in the existing optical PUF can only be used as a matrix material but cannot participate in the generation of optical anti-counterfeiting signals. It has significant innovation, practical value and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 is a schematic cross-sectional view of an optical PUF;

[0071] Figure 2 is a schematic diagram of a top view of a nano material composite film layer 2;

[0072] Figure 3 is a scanning electron microscope image of the nano material composite film layer 2;

[0073] Figure 4 is the scanning electron microscope image of SiO2 when the ammonia concentration is 0.5 M;

[0074] Figure 5 This is the size statistical distribution diagram of SiO2 when the ammonia concentration is 0.5 M;

[0075] Figure 6 is the scanning electron microscope image of SiO2 when the ammonia concentration is 0.7 M;

[0076] Figure 7 This is the size statistical distribution diagram of SiO2 when the ammonia concentration is 0.7 M;

[0077] Figure 8 is the scanning electron microscope image of SiO2 when the ammonia concentration is 0.9 M;

[0078] Fig. 9 This is the size statistical distribution diagram of SiO2 when the ammonia concentration is 0.9 M;

[0079] Fig.10 is the transmission electron microscope image of SiO2 when the concentration of ammonia water is 0.5 M;

[0080] Fig.11 is the selected area electron diffraction pattern of SiO2 when the concentration of ammonia water is 0.5 M;

[0081] Fig.12 is the transmission electron microscope image of SiO2 when the concentration of ammonia water is 0.7 M;

[0082] Fig.13is the selected area electron diffraction pattern of SiO2 when the concentration of ammonia water is 0.7 M;

[0083] Fig.14 is the transmission electron microscope image of SiO2 when the concentration of ammonia water is 0.9 M;

[0084] Fig.15 is the selected area electron diffraction pattern of SiO2 when the concentration of ammonia water is 0.9 M;

[0085] Fig.16 X-ray diffraction patterns of SiO2 prepared with different ammonia concentrations;

[0086] Fig.17 Transmittance diagram of pure PDMS film and SiO2 / PDMS composite film;

[0087] Fig.18 Raman spectra of SiO2 prepared with different ammonia concentrations;

[0088] Fig.19 Raman spectra of pure PDMS film at different positions;

[0089] Fig. 20 Raman spectra of SiO2 / PDMS composite films at different positions;

[0090] Fig.21 Box plots of PDMS film and three optical PUFs;

[0091] Fig. 22 Schematic diagram of barcodes and QR codes generated by three optical PUFs;

[0092] Fig.23 is a statistical distribution diagram of the Raman signal intensity generated by the optical PUF at different positions;

[0093] Fig.24 The bit uniformity statistical distribution diagram of pure PDMS film and SiO2 / PDMS composite film;

[0094] Fig.25 is the similarity distribution diagram of optical PUF;

[0095] Fig.26 It is the Hamming distance distribution diagram of optical PUF;

[0096] Fig. 27The Raman spectrum of the optical PUF prepared by doping diamond with nitrogen vacancy color centers in PDMS according to the prior art literature; (Guo H, Qin Y, Wang Z, et al. Multilevel Encoding Physically Unclonable Functions Based on The Multispecies Structure in Diamonds[J]. Advanced Functional Materials, 2024, 34(15): 2304648.). DETAILED DESCRIPTION

[0097] Unless otherwise defined, the technical terms or scientific terms used in this patent document shall have the usual meanings understood by persons with ordinary skills in the field to which the invention belongs. The terms "upper", "lower", "left", "right", "inside", "outside", etc. used in the patent specification and claims of the present invention are only used to indicate relative position relationships. When the absolute position of the described object changes, the relative position relationship may also change accordingly. It is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In addition, the different positions described in the present invention refer to arbitrary positions selected when testing the composite film to be tested, such as Figure 2 It should be noted that the numbering of the positions is arbitrarily chosen.

[0098] Embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0099] The testing methods for each performance are as follows:

[0100] 1. Detection method of optical PUF structure based on Raman signal:

[0101] The multilayer structure and composite film morphology of the optical PUF were photographed by a scanning electron microscope of model JEOL JSMIT800, with an electron acceleration voltage of 5 kV and a working distance of 8 mm;

[0102] 2. Detection method of transmittance of substrate, PDMS and nanomaterial composite film layer:

[0103] The transmittance of the substrate and the PDMS nanomaterial composite film layer is detected by a UV-visible spectrophotometer of model SHIMADZU UV-3600 Plus;

[0104] 3. Detection method of average diameter and shape of nano-SiO2:

[0105] The nano-SiO2 is detected by a scanning electron microscope of model JEOL JSMIT800, with an electron acceleration voltage of 5 kV and a working distance of 8 mm, and then the particle size of the nano-SiO2 is counted to obtain the average diameter of the nano-SiO2; or the nano-SiO2 is detected by a transmission electron microscope, with an electron acceleration voltage of 200 kV, and then the particle size of the nano-SiO2 is counted to obtain the average diameter of the nano-SiO2;

[0106] 4. Detection method of amorphous nano-SiO2:

[0107] The amorphous state of the nano-SiO2 is measured by an X-ray diffractometer of model SHIMADZU XRD-7000; or the amorphous state of the nano-SiO2 is measured by the selected area electron diffraction function of a transmission electron microscope, and the electron acceleration voltage is 200 kV;

[0108] 5. Detection method of composite Raman signal generated at any point on the composite film layer of nanomaterials:

[0109] The optical anti-counterfeiting signal of the optical PUF is generated from the composite Raman signal of the nano-silica and the polydimethylsiloxane, and can be detected by a Raman signal detection instrument with a surface scanning function; in one embodiment of the present invention, the intensity of the composite Raman signal generated at any point on the nano-material composite film layer 2 can be detected by a confocal Raman system of model WITEC alpha 300R, and the excitation (challenge) condition is a laser with a central emission wavelength of 300 to 600 nm; preferably, the excitation (challenge) condition is a laser with a central emission wavelength of 532 nm. In the present invention, "point" and "position" have the same meaning, that is, "point 1" and "position 1" are equivalent, and any point on the nano-material composite film layer of the present invention is equal to any position on the nano-material composite film layer, such as Figure 2 shown.

[0110] 6. The detection method of the optical PUF image of the present invention is: first randomly select any point on the nanomaterial composite film layer, and then extract multiple adjacent points to form an area of ​​N×N points starting from the point, and detect the Raman signals of N×N points according to the method of detecting the Raman signal of any point in the detection method of Article 5. Finally, the Raman signal intensities of N×N points form an optical PUF image, wherein N is an integer and ≥2. The optical PUF image detected by the present invention is illustrated by taking an image composed of 20×20 points as an example.

[0111] 7. Bit-Uniformity (BU) detection method of optical PUF:

[0112]

[0113] in, s The number of bits per key, i.e. the number of bits per optical PUF output, K l express s The bit array l bit response;

[0114] 8. Similarity Index (SI) detection method of optical PUF:

[0115] The calculation formula of the similarity is:

[0116]

[0117] in, C is the matrix difference of the two optical PUF images after binarization. The digitized matrix of the two PUF images can be expressed as: , , A and B represent the digitized matrices of two optical PUF images, which represent the binary data of the images, where the value of each pixel is 0 or 1; C 0 is a matrix C The number of "0" in a mn and b mn is the pixel value at the corresponding position, where m represents the row number and n represents the column number.

[0118] 9. Detection method of Hamming distance between optical PUF chips:

[0119] The calculation formula of the inter-chip Hamming distance (Inter Hamming Distance, Inter-HD) is:

[0120]

[0121] in, q represents the total number of different optical PUFs, s represents the number of bits of each key, that is, the number of bits output by each optical PUF, HD(Ki, Kj): represents the Hamming distance between the s-bit keys Ki and Kj generated by the i-th and j-th optical PUFs;

[0122] 10. Detection method of intra-chip Hamming distance of optical PUF:

[0123] The calculation formula of the intra-chip Hamming distance (Intra-HD) is:

[0124]

[0125] in, m Indicates the number of repeated measurements, that is, the total number of times the optical PUF is tested. s represents the number of bits of each key, HD(K i , K i,t ) Represents the original key K i with t The key obtained from the measurement K i,t The Hamming distance between .

[0126] Example 1

[0127] The present invention provides a method for preparing an optical PUF based on a Raman signal, the preparation method comprising the following steps:

[0128] Step (1) 1.5 moles of methanol solution, ammonia water (NH3·H2O) and deionized water are mixed, and the concentration of ammonia water is 0.5 M. The mixed solution is stirred at a speed of 900 rpm and maintained at 50°C, and then methyl orthosilicate (TMOS) is added to the mixed solution formed by methanol, ammonia water and deionized water, and the volume ratio of methyl orthosilicate (TMOS) to the mixed solution formed by methanol, ammonia water and deionized water is 1:60, and stirring is continued for 1 hour, and the obtained milky white suspension is then centrifuged at 8000 rpm for 10 minutes to separate SiO2 nanoparticles, and the obtained nanoparticles are then dried in an oven at 80°C for 1 hour;

[0129] Step (2) PDMS and a curing agent (PDMS curing agent purchased from Dow Corning Corporation, USA) were mixed in a volume ratio of 10:1, stirred at a speed of 900 rpm, 1 mL of SiO2 ethanol solution with a concentration of 1 mg / mL was added dropwise to the mixture (mass ratio m(PDMS):m(SiO2) was 4825:1), and then the SiO2 / PDMS mixture was spin-coated onto a quartz glass sheet at a speed of 4000 rpm and an acceleration of 400 rpm for 60 seconds, and then the quartz glass sheet coated with the SiO2 / PDMS composite film was heated on a hot plate at 80°C for 30 minutes to form a SiO2 / PDMS composite film.

[0130] Results and analysis:

[0131] Embodiment 1 The detection method of the optical PUF structure is as described above. The cross-sectional schematic diagram of the optical PUF is as shown in the detection method 1. Figure 1As shown, it includes, from bottom to top, a substrate 1 and a nano material composite film layer 2;

[0132] The detection method of the transmittance of the substrate 1 in Example 1 is the same as the detection method 2 described above. The transmittance of the substrate 1 in Example 1 is 91%;

[0133] Example 1 The transmittance detection method of the nano material composite film layer 2 is as described above. The transmittance spectrum of the nano material composite film layer 2 is as shown in Fig.17 As shown, the transmittance of the nano-material composite film layer 2 in Example 1 is 91%;

[0134] Example 1 The method for detecting the transmittance of PDMS in the nanomaterial composite film layer 2 is as described above. The transmittance spectrum of PDMS in the nanomaterial composite film layer 2 is as shown in the detection method 2. Fig.17 As shown, the transmittance of PDMS in the nanomaterial composite film layer 2 of Example 1 is 95%;

[0135] The scanning electron microscope image of the top view of the nano-material composite film layer 2 of Example 1 is shown in FIG. Figure 3 As shown,

[0136] Example 1 The detection method of the average diameter of nano-SiO2 in the nano-material composite film layer 2 is as described in the detection method 3 above. The scanning electron microscopy image and the transmission electron microscopy image of the nano-SiO2 in the nano-material composite film layer 2 are respectively as shown in Figure 4 and Fig.10 As shown, the average diameter of nano-SiO2 in the nano-material composite film layer 2 of Example 1 is 70.7 nm ( Figure 5 );

[0137] Example 1 The detection method of the amorphous state of nano-SiO2 in the nano-material composite film layer 2 is as described in the detection method 4 above. The X-ray diffraction spectrum and selected area electron diffraction image of nano-SiO2 are respectively as follows: Fig.16 and Fig.11 As shown, the nano-SiO2 in the nano-material composite film layer 2 of Example 1 is amorphous;

[0138] Example 1 The detection method of the shape of nano-SiO2 in the nano-material composite film layer 2 is as described in the detection method 4 above. The scanning electron microscopy image and the transmission electron microscopy image of the nano-SiO2 in the nano-material composite film layer 2 are respectively as shown in Figure 4 and Fig.10 As shown, the nano-SiO2 in the nano-material composite film layer 2 of Example 1 is spherical;

[0139] The Raman signal of the optical PUF in Example 1 is detected as described in Method 5 above, and the Raman spectra of the optical PUF at different positions are as follows: Fig. 20 , Fig.23As shown, the Raman spectra of the optical PUF in Example 1 at different positions have different Raman signal intensities. In contrast, the Raman spectra of the pure PDMS film at different positions have almost the same Raman signal intensities ( Fig.19 ), the comparison between the two shows that the random embedding of SiO2 nanoparticles in PDMS can change the intensity of the PDMS Raman signal at different positions. In addition, compared with the Raman spectrum of pure SiO2 nanoparticles, the Raman spectrum shape of the optical PUF of the present invention is completely different from that of SiO2 nanoparticles ( Fig.18 ), which is similar to the Raman spectrum shape of pure PDMS film, but the Raman signal intensity has changed significantly, further illustrating that the optical anti-counterfeiting signal of the optical PUF of the present invention comes from PDMS and SiO2 nanoparticles. The SiO2 nanoparticles of the present invention are randomly embedded in PDMS and form a composite Raman signal through interaction and synergy. This proves that the optical PUF technology of the present invention uses PDMS to generate optical anti-counterfeiting signals, rather than just using PDMS as a matrix as in the prior art. It should be noted that Fig.19 and Fig. 20 The different positions of are not corresponding to each other, but are chosen arbitrarily;

[0140] The bit uniformity of the optical PUF in Example 1 is as described in the detection method 6 above, and the statistical distribution diagram of the bit uniformity of the optical PUF is as follows: Fig.24 As shown, the average bit uniformity of the optical PUF in Example 1 is 0.4997; Bit Uniformity Average: Bit uniformity refers to the distribution balance of 0 and 1 bits in the response generated by a physical unclonable function (PUF). The ideal value is 0.5.

[0141] The similarity of the optical PUF in Example 1 is as described in the detection method 7, and the optical PUF similarity distribution diagram is as follows: Fig.25 As shown in the figure, the average similarity of different optical PUFs in Example 1 is 51%, and the average similarity of the same optical PUF in Example 1 is 92%; Average Similarity of the Same Optical PUF: This indicator measures the consistency of the response of the same optical PUF when tested at different times. The ideal value is 100%. Average Similarity of Different Optical PUFs: This indicator measures the distinction between different PUFs. The ideal value is 50%, indicating that each PUF is unique and there is almost no similarity between different PUFs.

[0142] The Hamming distance between optical PUF chips in Example 1 is as described in the detection method 8 above, and the distribution diagram of the Hamming distance between optical PUF chips is as shown in Fig.26 As shown, the average value of the Hamming distance between different optical PUF chips in Example 1 is 0.4994; Inter-HD Average: The inter-HD distance measures the difference in response between different PUFs. The ideal value is 0.5.

[0143] The Hamming distance within the optical PUF in Example 1 is as described in the detection method 8 above, and the distribution diagram of the Hamming distance within the optical PUF is as shown in Fig.26 As shown, the average value of the intra-chip Hamming distance of different optical PUFs in Example 1 is 0.1294; Intra-HD Average: The intra-chip Hamming distance measures the difference in the response of the same PUF measured at different times or under different conditions. The ideal value is 0.

[0144] The above metrics and their ideal values ​​are generally considered standard in the field of information security and cryptography because they are directly related to the strength and reliability of security systems. The ideal value of each metric is based on the requirements for ensuring system security and functionality, which are well known and widely accepted in academic and industrial research.

[0145] Example 2

[0146] Referring to the preparation method of Example 1, the preparation method parameters are shown in Table 3.

[0147] Results and analysis: Example 2 reduces the stirring speed of the mixed solution in step (1) within the scope of the present invention, increases the amount of methyl orthosilicate added in step (1), reduces the ratio of PDMS to curing agent in step (2), reduces the concentration of SiO2 ethanol solution in step (2), reduces the amount of SiO2 ethanol solution added in step (2), reduces the spin coating time in step (2), reduces the spin coating speed in step (2), and reduces the heating time after spin coating in step (2). The average diameter of SiO2 in the nanomaterial composite film layer 2 obtained by Example 2 increases, so that the transmittance of the nanomaterial composite film layer 2 decreases, and the transmittance of PDMS in the nanomaterial composite film layer 2 decreases. The average value of bit uniformity, the average value of similarity of the same optical PUF, the average value of inter-chip Hamming distance, and the average value of intra-chip Hamming distance are not much different from the ideal value, and all have excellent anti-counterfeiting performance. The detection method of each performance is the same as the detection method of Example 1, and the various performances are shown in Table 4.

[0148] Example 3

[0149] Referring to the preparation method of Example 1, the preparation method parameters are shown in Table 3.

[0150] Results and analysis: Example 3 increases the stirring speed of the mixed solution in step (1) within the scope of the present invention, increases the amount of methyl orthosilicate added in step (1), reduces the ratio of PDMS to curing agent in step (2), reduces the concentration of SiO2 ethanol solution in step (2), reduces the amount of SiO2 ethanol solution added in step (2), reduces the spin coating time in step (2), reduces the spin coating speed in step (2), and reduces the heating time after spin coating in step (2). The average diameter of SiO2 in the nanomaterial composite film layer 2 obtained by Example 3 is reduced, so that the transmittance of PDMS in the nanomaterial composite film layer 2 is reduced, so that the average value of bit uniformity, the average value of similarity of the same optical PUF, the average value of Hamming distance between sheets, and the average value of Hamming distance within a sheet are not much different from the ideal value, and all have excellent anti-counterfeiting performance. The detection method of each performance is the same as the detection method of Example 1, and each performance is shown in Table 4.

[0151] Example 4

[0152] Referring to the preparation method of Example 1, the preparation method parameters are shown in Table 3.

[0153] Results and analysis: Example 4 increases the concentration of ammonia water in step (1), reduces the stirring speed of the mixed solution in step (1), increases the amount of methyl orthosilicate added in step (1), and reduces the mass ratio of polydimethylsiloxane (PDMS) and nano-silicon dioxide (SiO2) within the scope of the present invention. The average diameter of SiO2 in the nano-material composite film layer 2 obtained by Example 4 increases ( Figure 6 , Figure 7 , Fig.12 , Fig.13 ), so that the average value of bit uniformity, the average value of similarity of different optical PUFs, the average value of inter-chip Hamming distance, and the average value of intra-chip Hamming distance are not much different from the ideal value, and all have excellent anti-counterfeiting performance. The detection method of each performance is the same as the detection method of Example 1, and the various performances are shown in Table 4.

[0154] Example 5

[0155] Referring to the preparation method of Example 1, the preparation method parameters are shown in Table 3.

[0156] Results and analysis: Example 5 increases the concentration of ammonia water in step (1) within the scope of the present invention, increases the amount of methyl orthosilicate added in step (1), and reduces the mass ratio of polydimethylsiloxane (PDMS) and nano-silicon dioxide (SiO2). The average diameter of SiO2 in the nano-material composite film layer 2 obtained by Example 5 is increased, so that the transmittance of the nano-material composite film layer 2 is reduced, so that the average value of bit uniformity, the average value of similarity of different optical PUFs, the average value of inter-chip Hamming distance, and the average value of intra-chip Hamming distance are not much different from the ideal value, and all have excellent anti-counterfeiting performance. The detection method of each performance is the same as the detection method of Example 1, and the various performances are shown in Table 4.

[0157] Example 6

[0158] Referring to the preparation method of Example 1, the preparation method parameters are shown in Table 3.

[0159] Results and analysis: Example 6 increases the concentration of ammonia water in step (1) within the scope of the present invention, increases the stirring speed of the mixed solution in step (1), increases the amount of methyl orthosilicate added in step (1), and reduces the mass ratio of polydimethylsiloxane (PDMS) and nano-silicon dioxide (SiO2). The average diameter of SiO2 in the nano-material composite film layer 2 obtained by Example 6 is increased, so that the transmittance of the nano-material composite film layer 2 is reduced, so that the average value of bit uniformity, the average value of inter-chip Hamming distance, and the average value of intra-chip Hamming distance are not much different from the ideal value, and all have excellent anti-counterfeiting performance. The detection method of each performance is the same as the detection method of Example 1, and the various performances are shown in Table 4.

[0160] Example 7

[0161] Referring to the preparation method of Example 1, the preparation method parameters are shown in Table 3.

[0162] Results and analysis: Example 7, within the scope of the present invention, increases the concentration of ammonia water in step (1), decreases the stirring speed of the mixed solution in step (1), decreases the amount of methyl orthosilicate added in step (1), increases the ratio of PDMS to curing agent in step (2), increases the mass ratio of polydimethylsiloxane (PDMS) and nano-silicon dioxide (SiO2), increases the concentration of SiO2 ethanol solution in step (2), increases the amount of SiO2 ethanol solution added in step (2), increases the spin coating time in step (2), increases the spin coating speed in step (2), and increases the heating time after spin coating in step (2). The average diameter of SiO2 in the nano-material composite film layer 2 obtained by Example 7 increases ( Figure 8 , Fig. 9 , Fig.14 , Fig.15), so that the transmittance of the nano-material composite film layer 2 is reduced, so that the transmittance of the PDMS in the nano-material composite film layer 2 is reduced, so that the average value of the bit uniformity, the average value of the similarity of different optical PUFs, the average value of the similarity of the same optical PUF, the average value of the Hamming distance between chips, and the average value of the Hamming distance within the chip are not much different from the ideal value, and all have excellent anti-counterfeiting performance. The detection method of each performance is the same as the detection method of Example 1, and the various performances are shown in Table 4.

[0163] Example 8

[0164] Referring to the preparation method of Example 1, the preparation method parameters are shown in Table 3.

[0165] Results and analysis: Example 8 increases the concentration of ammonia water in step (1) within the scope of the present invention, decreases the amount of methyl orthosilicate added in step (1), increases the ratio of PDMS to curing agent in step (2), increases the mass ratio of polydimethylsiloxane (PDMS) to nano-silicon dioxide (SiO2), increases the concentration of SiO2 ethanol solution in step (2), increases the amount of SiO2 ethanol solution added in step (2), increases the spin coating time in step (2), increases the spin coating speed in step (2), and increases the heating time after spin coating in step (2). The average diameter of SiO2 in the nano-material composite film layer 2 obtained by Example 8 increases, so that the transmittance of the nano-material composite film layer 2 decreases, so that the transmittance of PDMS in the nano-material composite film layer 2 decreases, so that the average value of bit uniformity, the average value of similarity of different optical PUFs, the average value of similarity of the same optical PUF, the average value of Hamming distance between chips, and the average value of Hamming distance within chips are not much different from the ideal value, and all have excellent anti-counterfeiting performance. The detection methods of various properties are the same as those of Example 1, and the various properties are shown in Table 4.

[0166] Example 9

[0167] Referring to the preparation method of Example 1, the preparation method parameters are shown in Table 3.

[0168] Results and analysis: Example 9 increases the concentration of ammonia water in step (1) within the scope of the present invention, increases the stirring speed of the mixed solution in step (1), reduces the amount of methyl orthosilicate added in step (1), increases the ratio of PDMS to curing agent in step (2), increases the mass ratio of polydimethylsiloxane (PDMS) and nano-silicon dioxide (SiO2), increases the concentration of SiO2 ethanol solution in step (2), increases the amount of SiO2 ethanol solution added in step (2), increases the spin coating time in step (2), increases the spin coating speed in step (2), and increases the heating time after spin coating in step (2). The average diameter of SiO2 in the nano-material composite film layer 2 obtained by Example 9 increases, so that the transmittance of the nano-material composite film layer 2 decreases, so that the transmittance of PDMS in the nano-material composite film layer 2 decreases, so that the average value of bit uniformity, the average value of similarity of the same optical PUF, the average value of inter-chip Hamming distance, and the average value of intra-chip Hamming distance are not much different from the ideal value, and all have excellent anti-counterfeiting performance. The detection methods of various properties are the same as those of Example 1, and the various properties are shown in Table 4.

[0169] Example 10

[0170] Referring to the preparation method of Example 1, the preparation method parameters are shown in Table 3.

[0171] Results and analysis: Example 10 increases the concentration of ammonia water in step (1) within the scope of the present invention, decreases the stirring speed of the mixed solution in step (1), decreases the amount of methyl orthosilicate added in step (1), increases the ratio of PDMS to curing agent in step (2), increases the mass ratio of polydimethylsiloxane (PDMS) and nano-silicon dioxide (SiO2), increases the concentration of SiO2 ethanol solution in step (2), increases the amount of SiO2 ethanol solution added in step (2), increases the spin coating time in step (2), increases the spin coating speed in step (2), and increases the heating time after spin coating in step (2). The average diameter of SiO2 in the nano-material composite film layer 2 obtained by Example 10 increases, so that the transmittance of the nano-material composite film layer 2 decreases, so that the transmittance of PDMS in the nano-material composite film layer 2 decreases, so that the average value of bit uniformity, the average value of similarity of different optical PUFs, and the average value of Hamming distance within the chip are not much different from the ideal value, and all have excellent anti-counterfeiting performance. The detection methods of various properties are the same as those of Example 1, and the various properties are shown in Table 4.

[0172] Embodiment 11

[0173] Referring to the preparation method of Example 1, the preparation method parameters are shown in Table 3.

[0174] Results and analysis: Example 11 increases the concentration of ammonia water in step (1) within the scope of the present invention, reduces the amount of methyl orthosilicate added in step (1), increases the ratio of PDMS to curing agent in step (2), increases the mass ratio of polydimethylsiloxane (PDMS) and nano-silicon dioxide (SiO2), increases the concentration of SiO2 ethanol solution in step (2), increases the amount of SiO2 ethanol solution added in step (2), increases the spin coating time in step (2), increases the spin coating speed in step (2), and increases the heating time after spin coating in step (2). The average diameter of SiO2 in the nano-material composite film layer 2 obtained by Example 11 increases, so that the transmittance of the nano-material composite film layer 2 decreases, so that the transmittance of PDMS in the nano-material composite film layer 2 decreases, so that the average value of bit uniformity, the average value of similarity of different optical PUFs, and the average value of Hamming distance between sheets are not much different from the ideal value, and all have excellent anti-counterfeiting performance. The detection method of each performance is the same as the detection method of Example 1, and the various performances are shown in Table 4.

[0175] Example 12

[0176] Referring to the preparation method of Example 1, the preparation method parameters are shown in Table 3.

[0177] Results and analysis: Example 12 increases the concentration of ammonia water in step (1) within the scope of the present invention, increases the stirring speed of the mixed solution in step (1), reduces the amount of methyl orthosilicate added in step (1), increases the ratio of PDMS to curing agent in step (2), increases the mass ratio of polydimethylsiloxane (PDMS) and nano-silicon dioxide (SiO2), increases the concentration of SiO2 ethanol solution in step (2), increases the amount of SiO2 ethanol solution added in step (2), increases the spin coating time in step (2), increases the spin coating speed in step (2), and increases the heating time after spin coating in step (2). The average diameter of SiO2 in the nano-material composite film layer 2 obtained by Example 12 increases, so that the transmittance of the nano-material composite film layer 2 decreases, so that the transmittance of PDMS in the nano-material composite film layer 2 decreases, so that the average value of bit uniformity, the average value of similarity of the same optical PUF, the average value of inter-chip Hamming distance, and the average value of intra-chip Hamming distance are not much different from the ideal value, and all have excellent anti-counterfeiting performance. The detection methods of various properties are the same as those of Example 1, and the various properties are shown in Table 4.

[0178] Comparative Example 1 The preparation method and detection method are the same as those of Example 1, except that the mass ratio of polydimethylsiloxane (PDMS) to nano-silicon dioxide (SiO2) (m(PDMS)∶m(SiO2)) is 380∶1.

[0179] Results and analysis: The transmittance of the nano-material composite film layer 2 obtained by comparative example 1 was reduced to 70%, affecting the optical properties. The average value of bit uniformity was reduced to 0.3587, the average values ​​of similarity between different and same optical PUFs were 54% and 81% respectively, and the Hamming distances were recorded as 0.3448 (inter-chip Hamming distance) and 0.2451 (intra-chip Hamming distance), respectively, which were far from the ideal Hamming distance. These deviations indicate that if the mass ratio of polydimethylsiloxane (PDMS) and nano-silicon dioxide (SiO2) (m(PDMS)∶m(SiO2)) is changed beyond the range described in the present invention, the optical PUF described in the present invention cannot be obtained. The detection method of the various properties of the optical PUF structure is the same as the detection method of Example 1, and the various properties are shown in Table 4.

[0180] Comparative Example 2 The preparation method and detection method are the same as those of Example 1, except that the mass ratio of polydimethylsiloxane (PDMS) to nano-silicon dioxide (SiO2) (m(PDMS)∶m(SiO2)) is 13000∶1.

[0181] Results and analysis: The average bit uniformity of the optical PUF obtained by comparative example 2 rises to 0.3982, and the similarity and Hamming distance of the optical PUF are very different from the ideal values, recorded as 55% (different PUF), 82% (same PUF), 0.3914 (inter-chip Hamming distance), and 0.2568 (intra-chip Hamming distance) respectively. This indicates that if the mass ratio of polydimethylsiloxane (PDMS) to nano-silicon dioxide (SiO2) (m(PDMS)∶m(SiO2)) exceeds the range described in the present invention, the optical PUF structure described in the present invention cannot be obtained. The detection method of each performance of the optical PUF is the same as the detection method of Example 1, and each performance is shown in Table 4.

[0182] Comparative Example 3 The preparation method and detection method are the same as those of Example 1, except that the nano-silicon dioxide is a crystalline material.

[0183] Results and analysis: The transmittance of the nano-material composite film layer 2 of the optical PUF obtained by comparative example 3 is reduced to 83%, and the average bit uniformity is 0.3591, the average similarity of different optical PUFs is 54%, the average similarity of the same optical PUF is 84%, the average Hamming distance between chips is 0.3489, and the average Hamming distance within the chip is 0.2481. It means that if the nano-silicon dioxide is a crystalline material, the optical PUF described in the present invention cannot be obtained. The detection method of the various properties of the optical PUF is the same as the detection method of Example 1, and the various properties are shown in Table 4.

[0184] Comparative Example 4 The main preparation method is the same as that of Example 1. The only difference in the preparation method is that silicon dioxide is not embedded in PDMS to form a composite film, but silicon dioxide and PDMS form two thin films respectively. The detection method is the same as that of Example 1.

[0185] Results and analysis: The optical PUF obtained by comparative example 4 is an independent layered structure, and the two layers of materials cannot form a microscopic interaction. When detecting the Raman signal, the intensity of the Raman signal generated at any different position is the same as that generated by pure PDMS. That is to say, when silica and PDMS form two thin films respectively, silica cannot enhance the complexity of the pure PDMS Raman signal and cannot be used for the optical PUF described in the present invention. After detection, the average bit uniformity is 0.2112, the average similarity of different optical PUFs is 95%, the average similarity of the same optical PUF is 96%, the average Hamming distance between chips is 0.0568, and the average Hamming distance within the chip is 0.0459. It means that if silica is not embedded in PDMS to form a composite film, but silica and PDMS form two thin films respectively, the optical PUF described in the present invention cannot be obtained. The detection method of each performance of the optical PUF is the same as the detection method of Example 1, and each performance is shown in Table 4.

[0186] Table 1 Make a 1.5 × 1.5 cm 2 Cost estimation of optical PUF of size

[0187]

[0188]

[0189] Table 2 Cost comparison of optical PUF manufactured by different methods

[0190]

[0191] Table 3 Optical PUF preparation parameters

[0192]

[0193] Table 4 Optical PUF performance parameters

[0194]

[0195] Summary and analysis:

[0196] By analyzing Examples 1-12 and Comparative Examples 1-4, it can be seen that the mass ratio of polydimethylsiloxane (PDMS) to nano-silicon dioxide (SiO2) (m(PDMS)∶m(SiO2)), the crystalline state of silicon dioxide and other parameters must be controlled to randomly embed nano-silicon dioxide into polydimethylsiloxane to form a composite film, so that the optical PUF can be precisely controlled. That is, the present invention forms the nano-material composite film layer by randomly embedding a specific proportion of nano-silicon dioxide into the PDMS matrix. The nano-silicon dioxide can be synergistically superimposed with the Raman signal of PDMS through interaction to form a composite Raman signal, so that any different position on the optical PUF is at the peak position of the Raman signal of polydimethylsiloxane (usually 490±5 cm -1 ) have different Raman signal intensities. The complexity of the Raman signal of the PDMS film is enhanced by the non-uniformly distributed nano-SiO2 particles, so that the average bit uniformity of the optical PUF of the present invention is between 0.49 and 0.51, the average similarity of different optical PUFs is between 49% and 53%, the average Hamming distance between chips is between 0.4 and 0.6, the average similarity of the same optical PUF is between 90% and 100%, and the average Hamming distance within the chip is between 0 and 0.2, realizing an optical PUF with excellent anti-counterfeiting performance and not affecting the accuracy and reliability of the biochip, and overcoming the technical prejudice that PDMS in the existing optical PUF can only be used as a matrix material and cannot participate in the generation of anti-counterfeiting signals. The above features of the present invention have a synergistic effect. If one of the conditions is changed beyond the scope described in the present invention, an optical PUF that meets the performance of the present invention cannot be obtained.

[0197] The above embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the present application.

Claims

1. An optical PUF based on Raman signal, characterized in that: The optical PUF comprises a nano-material composite film layer, wherein the nano-material composite film layer is a composite film formed by randomly embedding nano-silicon dioxide in polydimethylsiloxane, and the transmittance of the nano-material composite film layer and the polydimethylsiloxane in the wavelength range of 300 to 800 nm is ≥90%; the nano-silicon dioxide is an amorphous material; the mass ratio of the polydimethylsiloxane to the nano-silicon dioxide is m(PDMS):m(SiO2) of 400:1 to 10000:1; The optical anti-counterfeiting signal of the optical PUF is generated from the composite Raman signal of the nano-silicon dioxide and the polydimethylsiloxane, and there are differences in the Raman signal intensity at the peak of the Raman signal of polydimethylsiloxane at any different positions on the nano-material composite film layer.

2. The optical PUF according to claim 1, characterized in that The optical PUF further comprises a substrate, wherein the substrate is selected from materials having a transmittance of ≥90% within a wavelength range of 300-800 nm.

3. The optical PUF according to claim 2, characterized in that The substrate is selected from any one of quartz glass, sapphire, borosilicate glass, magnesium fluoride and calcium fluoride.

4. The optical PUF according to claim 1, characterized in that The nano silicon dioxide is spherical in shape and has an average diameter of 20 to 300 nm.

5. The optical PUF according to claim 1, characterized in that: The average value of the bit uniformity of the optical PUF is between 0.49 and 0.51; The calculation formula of the bit uniformity BU is: ,in, s The number of bits per key, i.e. the number of bits per optical PUF output, K l express s The bit array l bit response.

6. The optical PUF according to claim 1, characterized in that: The average similarity of different optical PUFs is between 49% and 53%, and the average similarity of the same optical PUF is between 90% and 100%. The calculation formula of the similarity SI is: ,in, C is the matrix difference of the two optical PUF images after binarization. The digitized matrix of the two PUF images can be expressed as: , , , A and B represent the digitized matrices of two optical PUF images, which represent the binary data of the images, where the value of each pixel is 0 or 1; C 0 is a matrix C The number of "0" in a mn and b mn is the pixel value at the corresponding position, where m represents the row number and n represents the column number.

7. The optical PUF according to claim 1, characterized in that The average value of the inter-chip Hamming distance of different optical PUFs is between 0.4 and 0.6, and the average value of the intra-chip Hamming distance of the same optical PUF is between 0 and 0.2; The calculation formula of the inter-chip Hamming distance Inter-HD is: ,in, q represents the total number of different optical PUFs, s represents the number of bits per key, i.e. the number of bits per optical PUF output, HD(K i , K j ) :Indicates the i and j An optical PUF is generated s Bit Key K i and K j The Hamming distance between The calculation formula of the intra-chip Hamming distance Intra-HD is: ,in, m Indicates the number of repeated measurements, that is, the total number of times the optical PUF is tested. s represents the number of bits of each key, HD(K i , K i,t ) Represents the original key K i with t The key obtained from the measurement K i,t The Hamming distance between .

8. A method for preparing an optical PUF based on Raman signals as claimed in claim 1, characterized in that: The preparation method comprises the following steps: Step (1) mixing an alcohol solution, ammonia water and deionized water to form a mixed solution, wherein the concentration of the ammonia water is 0.5 to 1 M, then adding methyl orthosilicate to the mixed solution in a volume ratio of 1:100 to 1:10, continuously stirring to obtain a milky white suspension, centrifuging to separate a solid, and then drying to obtain SiO2 nanoparticles; Step (2) polydimethylsiloxane (PDMS) and a curing agent are mixed in a volume ratio of 5:1 to 20:1, and then the SiO2 nanoparticles are added to the mixture of PDMS and the curing agent in a mass ratio of m(PDMS) to m(SiO2) of 400:1 to 10000:1 to obtain a SiO2 / PDMS mixture, and then the SiO2 / PDMS mixture is spin-coated onto a substrate at a speed of 3000 to 10000 rpm, and then heated at 40 to 100°C to form a SiO2 / PDMS composite film.

9. An anti-counterfeiting label, characterized in that: The anti-counterfeiting label comprises the optical PUF based on Raman signals according to any one of claims 1 to 7 or the optical PUF prepared by the preparation method according to claim 8.

10. Use of the optical PUF based on Raman signals according to any one of claims 1 to 7, the optical PUF based on Raman signals obtained by the preparation method according to claim 8, and the anti-counterfeiting label according to claim 9 in the field of anti-counterfeiting.